Factors affecting patient readiness and surgical outcomes in preoperative patients a model testing study - Torres, Gian Carlo Sy
Background: Surgery is a common approach to manage various disorders among patients across the lifespan. However, being an unknown and complex procedure for most, it may lead to stress and anxiety, both to the patient and their significant others. Nurses, being at the forefront of patient care, must ensure adequate preparation to promote patient readiness.Albeit studies claim the importance of readiness, there is paucity of evidence supporting such notion.